Produção biotecnológica de ácido itacônico a partir da casca de arroz - Pedroso, Giovanni Bressiani (2014)
Rice Husks (RH) can be regarded as an abundant lignocellulosic raw material in the Brazilian southern(se for somente regiões do RS, SC e PR fica South region, senão, tá ok) region, renewable and practically without economic added value able to be bioconverted into industrial and pharmochemical products of great interest. The main objective of this dissertation was to search the use of RH for the production of itaconic acid (IA) and, simultaneously, to contribute to the mitigation of a serious environmental problem arising from the improper disposal of the processing residues. For this, RHs were submitted to pressurized acid hydrolysis with diluted HNO3 and H3PO4in accordance with a statistical multivariate planning using Central Composite Rotatable Design (DCCR). The experiments showed that, at 145 °C and reaction time of 28 min, with 3,4% (v v-1) H3PO4, it was produced 44,4 g sugar L-1, by yield of 266,4 mg sugar g-1 RH. By using 3,76% (v v-1) HNO3, the best experimental was 135 ºC and reaction time of 35 min, resulting on a 42,0 g sugar L-1, by yield of 252,0 mg sugar g-1RH. Compared to the results obtained before in our group for chloridric RH hydrolysis, the outcomes of this work were better, considering the concomitant liberation of glucose, xylose and arabinose. However, no additional benefit was found by applying a RH pretreatment with NaOH and NH4OH. Previous fermentative tests were made to find the best conditions for the grown of the Aspergillus terreus (ATCC 7860) fungus in RH hydrolysate, submitting the fermentative process to a central compound experimental design in blocks, evaluating the variables initial pH, temperature, use of yeast extract (YE) and RH origin. 20 mL flasks were used for the batch experiments. The best experiment produced 1,9 g IA L-1, by yield of 132 mg AI g-1 sugars (or 11,4 mg AI g-1 RH), using chloridric hydrolysate (0,8% HCl v v-1), 145 ºC and reation time of 46 min; detoxification with CaO, fermentation medium 50:50 hydrolysate : potato dextrose solution, with 10,0 g YE L-1, initial pH 6,0, 152 h fermentation). The used analytical techniques were HPLC-DAD and -RID, and UV-visible spectrophotometry, including the figures-of-merit and validation of the developed methodologies. It was possible to demonstrate the viability of the production processes of IA from RH, in laboratory scale, contributing to the efforts to the development of the biotechnological research and scientific innovation.